Mouse polyomavirus enters early endosomes, requires their acidic pH for productive infection, and meets transferrin cargo in Rab11-positive endosomes - Liebl, David; Difato, Francesco; Horníková, Lenka; Mannová, Petra; Stokrová, Jitka; Forstová, Jitka (Journal of virology, 2006)
Mouse polyomavirus (PyV) virions enter cells by internalization into smooth monopinocytic vesicles, which fuse under the cell membrane with larger endosomes. Caveolin-1 was detected on monopinocytic vesicles carrying PyV particles in mouse fibroblasts and epithelial cells (33). Here, we show that PyV can be efficiently internalized by Jurkat cells, which do not express caveolin-1 and lack caveolae, and that overexpression of a caveolin-1 dominant-negative mutant in mouse epithelial cells does not prevent their productive infection. Strong colocalization of VP1 with early endosome antigen 1 (EEA1) and of EEA1 with caveolin-1 in mouse fibroblasts and epithelial cells suggests that the monopinocytic vesicles carrying the virus (and vesicles containing caveolin-1) fuse with EEA1-positive early endosomes. In contrast to SV40, PyV infection is dependent on the acidic pH of endosomes. Bafilomycin A1 abolished PyV infection, and an increase in endosomal pH by NH4Cl markedly reduced its efficiency when drugs were applied during virion transport towards the cell nucleus. The block of acidification resulted in the retention of a fraction of virions in early endosomes. To monitor further trafficking of PyV, we used fluorescent resonance energy transfer (FRET) to determine mutual localization of PyV VP1 with transferrin and Rab11 GTPase at a 2- to 10-nm resolution. Positive FRET between PyV VP1 and transferrin cargo and between PyV VP1 and Rab11 suggests that during later times postinfection (1.5 to 3 h), the virus meets up with transferrin in the Rab11-positive recycling endosome. These results point to a convergence of the virus and the cargo internalized by different pathways in common transitional compartments.
Keywords: transport proteinů; transferin; endozomy; Endosomes; Microscopy, Electron; Rab proteiny vázající GTP; Transferrin; Protein Transport; Protein Binding; virion; fúze membrán; rab GTP-Binding Proteins; zvířata; Membrane Fusion; myši; Caveolin 1; Polyomavirus; časové faktory; Mice; buněčné linie; rezonanční přenos fluorescenční energie; Cell Line; Virion; vazba proteinů; Hydrogen-Ion Concentration; elektronová mikroskopie; Animals; Fluorescence Resonance Energy Transfer; koncentrace vodíkových iontů; Time Factors; kaveolin 1